Space for Media and Digital Literacy in the Context of Primary Education - Karasová, Mária; Uhrinová, Miriam (Journal of Education, Technology and Computer Science, 2021)
The contribution focuses on current questions and issues in the area of mass media influence on the behaviour of pupils of a younger school age in Slovakia. It offers partial results of research that appeal not only to the importance of implementing media education into primary education, but also show the real status of teachers’ readiness in the area of digital and media literacy. Research was quantitative-qualitative and in addition to the questionnaire method was realised interviews with headteachers of schools and focus interviews with the pupils. The aim of our research probing was to find out the contemporary state of the implementation of the media education into the education process as well as preparation of the teachers in the educational practices in regard to the specific sphere. Research is currently continuing to diagnose the digital literacy of teachers and future teachers in Slovakia.